The impacts of urban location on the involvement of knowledge-intensive services in international innovation collaboration - Bernd Ebersberger; Sverre Herstad (European Regional Science Association (ERSA), 2012)
Research on territorial innovation systems has traditionally put a very strong emphasis on intra-economy collaborative linkages as they allow valuable tacit knowledge to flow between co-located firms and institutions. Frequent face-to-face contact between producers and demanding users combined with institutionalized trust nurtured by proximity has been seen as conducive to advanced new knowledge development, structural change and growth. This is visible not least in the literature on knowledge-intensive business services, which emphasizes the role of proximity between providers and a demanding client base. However, collaborative linkages can span large distances and are increasingly regarded as a mechanism by which firms overcome local supply and demand side limitations. The rapid diffusion of ICTs has increased the scope for service firm, by increasing tradability and by allowing more efficient international market search. At the same time, regions remain important as `containing social structures' for labor flows and information diffusion through interpersonal networks, for new firm formation based on localized knowledge assets, and as platforms for growth and internationalization. The locus of innovation is therefore shifting away from individual firms, towards territorial economies and the distributed innovation networks by which they are linked. Knowledge intensive business services are important in this context, as they are positioned at the intersection between corporate demand for specialized knowledge, and the supply of this knowledge from various actors and locations. Yet, the literature on internationalization in services focuses primarily on demand side enablers in the form of trade liberalization and modern ICTs, and drivers in the form of larger and more diverse markets. Consequently, it has yet to acknowledge the embeddedness of knowledge-intensive business services in international innovation collaboration networks more broadly. This paper starts from the recognition that collaborative linkages may be conditioned by contexts of location, in particular when they are extended into distant business communities. This paper analyses the link between urban locations, and the involvement of knowledge-intensive business service firms in international innovation collaboration. It extends current research on the internationalization of business services by distinguishing between demand and supply side linkages in international innovation collaboration. The empirical analysis uses establishment level innovation data available from the Sixth Norwegian Community Innovation Survey (CIS2008) to investigate whether urban location affects a firm's involvement in global innovation collaboration. Everything else equal knowledge-intensive business service firms located in the Norwegian capital region are found to be more involved in international collaboration than establishments located at any other level of centrality. This is not driven by the more intense interaction with clients and customers. Rather, it is most distinctively driven by broader linkages with knowledge supplying actors.
Keywords: R11F20L80; 330; Internationalization of innovation; KIBS; urban location